Meningkatkan Peran Pemuda dalam Pembangunan Lingkungan Melalui Tugas sebagai Ketua RT - Usnan Usnan (UIN Raden Mas Said Surakarta, 2021)
Youth is a great asset as a source of development of a nation, so that the participation and role of youth needs to be maintained and enhanced. Based on this urgency, the community service activities carried out by the author in his position as head of RT in Dukuh Plembon, Kepanjen, Delanggu, Klaten, made efforts to increase the role of youth in environmental development by initiating the formation of youth organizations at the RT 04 level.Â The results obtained from these activities were that the author could carry out the target of achieving activities starting from the preparation stage, the stage of forming a youth organization until the assistance process. The real results of the three stages carried out by the author were the formation of the RT 04 youth organization with several activities that have been successfully carried out by the RT 04 youth organization, namely; (1) internal activities of youth organizations including meetings monthly and regulary contributions, and (2) external activities as a form of youth concern for the community and the environment including synergy with the RT program, community service monthly and making sign of street at RT 04.